Polymer gels for solar-driven interfacial evaporation - Ningning Ma; Ning’er Xie; Naifang Zhang; Xiangjiu Guan (Next Materials)
Solar-driven interfacial evaporation (SDIE), with merits of high evaporation efficiency, rapid response time, minimal pollution and straightforward system, has emerged as a promising approach to address the critical issue of freshwater scarcity. Among the various materials investigated, polymer-based gels have emerged as excellent candidate for solar evaporation. Based on the highly tunable molecular structures, interconnected porous channels, and inherent hydrophilicity, polymer gel could efficiently convert the absorbed sunlight into heat via incorporating light-absorbing particles or molecules into the gel matrix, hence promoting rapid evaporation. This review provides an overview of polymer gels in the field of interfacial evaporation, focusing on the structure regulation, crosslinking mechanism and design strategies for solar evaporators. The research progress on applications of polymer-based gels is also discussed, including seawater desalination, wastewater treatment, water-electricity co-production, water-hydrogen co-production and the extraction of rare metals. Additionally, the challenges and opportunities for polymer-based solar evaporators are addressed in the context of sustainable development.